Making waves: toward systems-level interpretation of hormonal and endogenous biomarkers in wastewater-based epidemiology - Ahmed S. Abouhend; Walid A. Hanafy; Christopher Watt; Raphael C. Nnachi; Prashant Shenoy; Caitlyn S. Butler (Water Research, 2026)

Performance of summary measures of core body temperature in heat-related health outcome regression models - M. Dally; A. Dye-Robinson; Y. Li; D. Jaramillo; K. Villarreal-Hernandez; L. Krisher; J. Butler-Dawson; J. Schaeffer; J. L. Adgate; K. A. James; L. S. Newman (International Journal of Biometeorology, 2025)

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The origin and water quality of spring systems in Monchique, Portugal: A focus on Long-Term sustainability and elevated sodium levels - M.A. Hoque; K.B. Amponsah; A. Blum; N. Walton; P. Dennis; A.P. Butler; S. Hugman; A. Bamberger; M. Fowler (Journal of Hydrology, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Feasibility and Tolerability of Daily Microgreen Consumption in Healthy Middle-Aged/Older Adults: A Randomized Crossover Trial - S. Holmes; K. Michell; M. Butler; B. Smith; A. Vazquez; E. Woolf; L. Grabos; S. Lee; S. Newman; M. Uchanski; T. Weir; S. Johnson (Journal of the Academy of Nutrition and Dietetics, 2023)

Qualities Preceptors Prefer in a Dietetic Intern - W. Koszewski; C. Butler; M. Doyle; A. Wise; S. Nielsen (Journal of the Academy of Nutrition and Dietetics, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

Urinary concentrations of metals before and after volcanic eruption: a natural experiment surrounding the eruption of Volcán de Fuego, 2018 - Natalie R. Neumann; Jaime Butler-Dawson; Lyndsay Krisher; Diana Jaramillo; Daniel Pilloni; Greg Waite; Yaqiang Li; Stephen B. Wittels; Kathrin Schilling; Lee S. Newman; Katherine A. James (Environmental Geochemistry and Health, 2023)

Genetic variation in fire recovery and other fire-related traits in a global eucalypt species - Mariano A. Hernández; Jakob B. Butler; Hans Ammitzboll; Jules S. Freeman; Julianne O’Reilly-Wapstra; René E. Vaillancourt; Brad M. Potts (Tree Genetics & Genomes, 2022)
To understand the potential of forests to adapt to wildfire, we studied the genetic architecture of fire-related structural, damage and recovery traits in a globally important Australian forest tree species, Eucalyptus globulus . Fourteen traits were evaluated in an outcrossed F 2 population in a field trial in Tasmania, Australia, which was burnt by a wildfire 14 years after planting. The trial also included open-pollinated families of the grandparental dwarf and tall ecotypes used to produce the F 2 population. We studied the phenotypic correlations within the F 2 population and performed quantitative trait loci (QTL) analyses using a linkage map comprised of 472 markers. Ecotype comparisons revealed that almost all traits were under genetic control, with trees of the dwarf ecotype significantly more damaged and mainly recovering from lignotubers, whereas tall ecotype trees mainly recovered from epicormic resprouts extending for a variable height up the stem. Within the F 2 , tree size was negatively correlated with fire damage and positively correlated with recovery. Genetic control of fire-related traits was confirmed by the detection of 38 QTL in the F 2 population. These QTL accounted for 4 to 43% of the phenotypic variation in these traits. Several QTL co-located and likely reflect pleiotropic effects. However, many independent QTL were detected, including QTL for crown consumption and trunk scorch, epicormic resprouting, resprout herbivory, and seedling establishment. The QTL detected argue that many genetically controlled mechanisms are responsible for variation in fire damage and recovery.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Towards open-source LOD2 modelling using convolutional neural networks - H. Muftah; T. S. L. Rowan; A. P. Butler (Modeling Earth Systems and Environment, 2022)
The aim of this paper is to classify and segment roofs using vertical aerial imagery to generate three-dimensional (3D) models. Such models can be used, for example, to evaluate the rainfall runoff from properties for rainwater harvesting and in assessing solar energy and roof insulation options. Aerial orthophotos and building footprints are used to extract individual roofs and bounding boxes, which are then fed into one neural network for classification and then another for segmentation. The approach initially implements transfer learning on a pre-trained VGG16 model. The first step achieves an accuracy of 95.39% as well as a F 1 score of 95%. The classified images are segmented using a fully convolutional network semantic segmentation model. The mask of the segmented roof planes is used to extract the coordinates of the roof edges and the nexus points using the Harris corner detector algorithm. The coordinates of the corners are then used to plot a 3D Level of Detail 2 (LOD2) representation of the building and the roof height is determined by calculating the maximum and minimum height of a Digital Surface Model LiDAR point cloud and known building height data. Subsequently the wireframe plot can be used to compute the roof area. This model achieved an accuracy of 80.2%, 96.1%, 96.0%, 85.1% and 91.1% for flat, hip, gable, cross-hip and mansard roofs, respectively.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Combined visual and biochemical analyses confirm depositor and diet for Neolithic coprolites from Skara Brae - Andrzej A. Romaniuk; Elsa Panciroli; Michael Buckley; Manasij Pal Chowdhury; Carla Willars; Jeremy S. Herman; Lore G. Troalen; Alexandra N. Shepherd; David V. Clarke; Alison Sheridan; Bart E. van Dongen; Ian B. Butler; et al. (Archaeological and Anthropological Sciences, 2020)
Coprolites (fossilized faeces) can provide valuable insights into species’ diet and related habits. In archaeozoological contexts, they are a potential source of information on human-animal interactions as well as human and animal subsistence. However, despite a broad discussion on coprolites in archaeology, such finds are rarely subject to detailed examination by researchers, perhaps due to the destructive nature of traditional analytical methods. Here, we have examined coprolitic remains from the Neolithic (third millennium BCE) settlement at Skara Brae, Orkney, using a range of modern methods: X-ray computed tomography, scanning electron microscopy, lipid and protein analysis (shotgun proteomics of the coprolite matrix as well as collagen peptide mass fingerprinting of isolated bone fragments). This combined approach minimised destructiveness of sampling, leaving sufficient material for subsequent study, while providing more information than traditional morphological examination alone. Based on gross visual examination, coprolites were predominantly attributed to domestic dogs ( Canis familiaris ), with morphologically identified bone inclusions derived from domestic sheep ( Ovis aries ) and common voles ( Microtus arvalis ). Partial dissection of a coprolite provided bone samples containing protein markers akin to those of domestic sheep. Considering the predominance of vertebral and distal limb bone fragments, Skara Brae dogs were probably consuming human butchery or meal refuse, either routinely fed to them or scavenged. The presumably opportunistic consumption of rodents may also have played a role in pest control.

Chromium, manganese, nickel, and cobalt mobility and bioavailability from mafic-to-ultramafic mine spoil weathering in western Massachusetts, USA - Justin A. Mistikawy; Trevor J. Mackowiak; Mark J. Butler; Ivan C. Mischenko; Richard S. Cernak; Justin B. Richardson (Environmental Geochemistry and Health, 2020)

Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Manuel Bellanger; Cameron Speir; Fabian Blanchard; Kate Brooks; James R. A. Butler; Scott Crosson; Robert Fonner; Sophie Gourguet; Daniel S. Holland; Sakari Kuikka; Bertrand Le Gallic; Rebecca Lent; et al. (Frontiers in Marine Science, 2020)

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Evaluating the effects of catch-and-release angling on Cape stumpnose Rhabdosargus holubi in a South African estuary - NK Arkert; A-R Childs; MC Parkinson; AC Winkler; E Butler; S Mannheim; WM Potts (African Journal of Marine Science, 2018)

Chromatographic fingerprinting of Lupinus luteus L. (Leguminosae) main secondary metabolites: a case of domestication affecting crop variability - Claudia E. Osorio; Veronique S. E. Amiard; Javiera Aravena-Calvo; Joshua A. Udall; Jeff J. Doyle; Iván J. Maureira-Butler (Genetic Resources and Crop Evolution, 2018)

Vulnerability of the livestock industry in eastern Australia - N. A. Marshall; B. M. Taylor; S. Heyenga; D. Butler (Sustainability Science, 2018)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Wheat cultivar susceptibility to Gaeumannomyces graminis var. tritici and influence on Pseudomonas fluorescence numbers in the rhizosphere - R. F. van Toor; S. Chng; R. M. Warren; R. C. Butler; M. G. Cromey; R. A. Craigie; B. L. McCloy (Australasian Plant Pathology, 2016)

Using a model based fourth-corner analysis to explain vegetation change following an extraordinary fire disturbance - S. E. Venn; C. M. Pickering; S. A. Butler; A. D. Letten (Oecologia, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Quantitative PCR to detect Gaeumannomyces graminis var. tritici in symptomatic and non-symptomatic wheat roots - S. Keenan; M. G. Cromey; S. A. Harrow; S. L. Bithell; R. C. Butler; S. S. Beard; A. R. Pitman (Australasian Plant Pathology, 2015)

A simple and inexpensive enteric-coated capsule for delivery of acid-labile macromolecules to the small intestine - Darren S. Miller; Anne Michelle Parsons; John Bresland; Paul Herde; Duc Minh Pham; Angel Tan; Hung-yao Hsu; Clive A. Prestidge; Tim Kuchel; Rezaul Begg; Syed Mahfuzul Aziz; Ross N. Butler (Journal of Zhejiang University-SCIENCE B, 2015)

Scaffolds for Tendon and Ligament Repair and Regeneration - Anthony Ratcliffe; David L. Butler; Nathaniel A. Dyment; Paul J. Cagle; Christopher S. Proctor; Seena S. Ratcliffe; Evan L. Flatow (Annals of Biomedical Engineering, 2015)

Compounds alone and in combination with yeasts to control Colletotrichum acutatum in apples - Kirsty S. H. Boyd-Wilson; Ruth C. Butler; Peter A. Alspach; Kerry R. Everett; I. P. Shamini Pushparajah; Monika Walter (Australasian Plant Pathology, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Larval Distribution and Behavior of Chrysomya rufifacies (Macquart) (Diptera: Calliphoridae) Relative to Other Species on Florida Black Bear (Carnivora: Ursidae) Decomposing Carcasses - S L Swiger; J A Hogsette; J F Butler (Neotropical Entomology, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Physiological and functional evaluation of healthy young and older men and women: design of the European MyoAge study - Jamie S. McPhee; Jean-Yves Hogrel; Andrea B. Maier; Enn Seppet; Olivier R. Seynnes; Sarianna Sipilä; Roberto Bottinelli; Yoann Barnouin; Astrid Y. Bijlsma; Helena Gapeyeva; Thomas M. Maden-Wilkinson; Carel G. Meskers; et al. (Biogerontology, 2013)

Circulating levels of adipokines and IGF-1 are associated with skeletal muscle strength of young and old healthy subjects - Laura Bucci; Stella Lukas Yani; Cristina Fabbri; Astrid Y. Bijlsma; Andrea B. Maier; Carel G. Meskers; Marco V. Narici; David A. Jones; Jamie S. McPhee; Enn Seppet; Helena Gapeyeva; Mati Pääsuke; et al. (Biogerontology, 2013)

Skeletal muscle adaptations to physical inactivity and subsequent retraining in young men - E. L. Campbell; O. R. Seynnes; R. Bottinelli; J. S. McPhee; P. J. Atherton; D. A. Jones; G. Butler-Browne; M. V. Narici (Biogerontology, 2013)

Effects of different rates of Gaeumannomyces graminis var. tritici inoculum for detecting take-all suppression in soils - S. F. Chng; A. Stewart; M. G. Cromey; S. L. Dodd; R. C. Butler; M. V. Jaspers (Australasian Plant Pathology, 2013)

Green and black tea intake in relation to prostate cancer risk among Singapore Chinese - Julia A. Montague; Lesley M. Butler; Anna H. Wu; Jeanine M. Genkinger; Woon-Puay Koh; Alvin S. Wong; Renwei Wang; Jian-Min Yuan; Mimi C. Yu (Cancer Causes & Control, 2012)

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Generation of antibody- and B cell-deficient pigs by targeted disruption of the J-region gene segment of the heavy chain locus - M. Mendicino; J. Ramsoondar; C. Phelps; T. Vaught; S. Ball; T. LeRoith; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; et al. (Transgenic Research, 2011)

Targeted disruption of the porcine immunoglobulin kappa light chain locus - J. Ramsoondar; M. Mendicino; C. Phelps; T. Vaught; S. Ball; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; N. Wertz; et al. (Transgenic Research, 2011)

Leptidea sinapis (Wood White butterfly) egg-laying habitat and adult dispersal studies in Herefordshire - S. A. Clarke; D. G. Green; J. Joy; K. Wollen; I. Butler (Journal of Insect Conservation, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Association of common DNA sequence variants at 33 genetic loci with blood lipids in individuals of African ancestry from Jamaica - R. Gupta; K. Ejebe; J. Butler; G. Lettre; H. Lyon; C. Guiducci; R. Wilks; F. Bennett; T. Forrester; B. Tayo; K. Musunuru; J. Hirschhorn; et al. (Human Genetics, 2010)

Improving the Performance of the Roundtable on Sustainable Palm Oil for Nature Conservation - WILLIAM F. LAURANCE; LIAN P. KOH; RHETT BUTLER; NAVJOT S. SODHI; COREY J. A. BRADSHAW; J. DAVID NEIDEL; HAZEL CONSUNJI; JAVIER MATEO VEGA (Conservation Biology, 2010)

Analysis of flow processes in fractured chalk under pumped and ambient conditions (UK) - A. P. Butler; S. A. Mathias; A. J. Gallagher; D. W. Peach; A. T. Williams (Hydrogeology Journal, 2009)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

Genetic inactivation of acetylcholinesterase causes functional and structural impairment of mouse soleus muscles - A. Vignaud; F. Fougerousse; E. Mouisel; N. Guerchet; C. Hourde; F. Bacou; G. S. Butler-Browne; A. Chatonnet; A. Ferry (Cell and Tissue Research, 2008)

A Greenhouse Assay for Powdery Scab (Spongospora subterranea f. sp. subterranea) Resistance in Potato - S. J. Baldwin; R. A. Genet; R. C. Butler; J. M. E. Jacobs (Potato Research, 2008)

Visual cortex activation in kinesthetic guidance of reaching - W. G. Darling; R. J. Seitz; S. Peltier; L. Tellmann; A. J. Butler (Experimental Brain Research, 2007)

Life Cycle Impact Assessment of Greywater Recycling Technologies for New Developments - F. A. Memon; Z. Zheng; D. Butler; C. Shirley-Smith; S. Lui; C. Makropoulos; L. Avery (Environmental Monitoring and Assessment, 2007)

Transgenic Potato Lines Expressing cry1Ba1 or cry1Ca5 Genes are Resistant to Potato Tuber Moth - S. Meiyalaghan; J. M. E. Jacobs; R. C. Butler; S. D. Wratten; A. J. Conner (Potato Research, 2007)

Modelling the impacts of removing seal predation from Atlantic salmon, Salmo salar , rivers in Scotland: a tool for targeting conflict resolution - J. R. A. BUTLER; S. J. MIDDLEMAS; I. M. GRAHAM; P. M. THOMPSON; J. D. ARMSTRONG (Fisheries Management and Ecology, 2006)
Bioenergetics were used to model the potential impacts on adult Atlantic salmon, Salmo salar L., stocks and rod fisheries of removing harbour seals, Phoca vitulina L., from three rivers of different scales in the Moray Firth, Scotland, viz: the Spey (large), Conon (medium) and Moriston (small). Overall, seals had the greatest impact on the Moriston, where removal of a single animal could increase cumulative catch by 17% during the fishing season. On the Conon and Spey the impacts were negligible, and resulted in increased catches of 33% in rivers with monthly rod catches ≤10 fish, but declined to 34 fish. The outputs of the models are qualitative, but provide a management tool for targeting action to resolve seal‐salmon fishery conflict. Smaller salmon population units, and spring salmon sub‐stocks and fisheries in particular, are most vulnerable to predation. The merit of this approach is discussed regarding the management of Special Areas of Conservation for salmon and seals.

Accounting for body condition improves allometric estimates of resting metabolic rates in fasting king penguins, Aptenodytes patagonicus - A. Fahlman; L. G. Halsey; P. J. Butler; D.R. Jones; A. Schmidt; S. Durand; G. Froget; C. -A. Bost; A. J. Woakes; C. Duchamp; Y. Handrich (Polar Biology, 2006)

Free-range Village Chickens on the Accra Plains, Ghana:Their Husbandry and Productivity - P. A. T. Aboe; K. Boa-Amponsem; S. A. Okantah; E. A. Butler; P. T. Dorward; M. J. Bryant (Tropical Animal Health and Production, 2006)

Air temperatures at Armagh Observatory, Northern Ireland, from 1796 to 2002 - C. J. Butler; A. M. García Suárez; A. D. S. Coughlin; C. Morrell (International Journal of Climatology, 2005)
Three independent mean temperature series for Armagh Observatory, covering the period 1796–2002 have been calibrated and corrected for the time of reading and exposure. Agreement between the three series is good in regions of overlap. With a short gap in the Armagh data from 1825 to 1833 filled by data from two stations in Dublin, the resulting series is the longest for the island of Ireland and one of the longest for any single site in the British Isles. Over the past 207 years, we note that temperatures in Armagh, in all seasons, show a gradual overall trend upwards. However, there are seasonal differences: summer and spring temperatures have increased by only half as much as those in autumn and winter. This is partly due to the exceptionally cold winters and autumns experienced prior to 1820. Relative to the overall trend, warm periods occurred in Ireland, as in other parts of Europe, in the mid‐19th century, in the mid‐20th century and at the end of the 20th century. Relatively cool temperatures prevailed in the early 19th century, in the 1880s and in the 1970s. Thus, if the baseline against which current temperatures are compared were moved from the late 19th century to include the earlier warm period, the apparent warming at the end of the late 20th century would be correspondingly reduced. A gradual decline in the daily temperature range at Armagh since 1844 may have resulted from higher minimum temperatures associated with increased cloudiness. A 7.8 year periodicity is identified in winter and spring mean temperatures at Armagh, which is probably a consequence of the North Atlantic oscillation. Copyright © 2005 Royal Meteorological Society

Investigating the Relationship Between Site-specific Yield and Protein of Cereal Crops - S. Norng; A. N. Pettitt; R. M. Kelly; D. G. Butler; W. M. Strong (Precision Agriculture, 2005)

Reduced metaphase I associations between the short arms of homoeologous chromosomes in a Hordeum vulgare L. H. bulbosum L. diploid hybrid influences the frequency of recombinant progeny - R. A. Pickering; S. Hudakova; A. Houben; P. A. Johnston; R. C. Butler (Theoretical and Applied Genetics, 2004)

Comparative In Vitro Surveillance of Amoxicillin-Clavulanic Acid and Four Oral Comparators Against 21,232 Clinical Isolates from Europe - D. J. Hoban; S. K. Bouchillon; J. L. Johnson; G. G. Zhanel; D. L. Butler; K. A. Saunders; L. A. Miller; J. A. Poupard (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Task-dependent control of human masseter muscles from ipsilateral and contralateral motor cortex - Sophie L. Butler; Timothy S. Miles; Philip D. Thompson; Michael A. Nordstrom (Experimental Brain Research, 2001)

Current and elevated levels of UV‐B radiation have few impacts on yields of perennial forage crops - Yousef A. Papadopoulos; Robert J. Gordon; Kenneth B. Mcrae; RoY. S. Bush; Gilles Bélanger; E. AnnE. Butler; Sherry A. E. Fillmore; Malcolm Morrison (Global Change Biology, 1999)
Summary Two experiments assessed the effect of current and elevated levels of ultraviolet B (UV‐B) radiation on forage crop production. The effect of current levels of UV‐B radiation was assessed by comparing the growth of eight cultivars of four legume and four grass species for three growing seasons (1994–96) under simulated sward conditions in the field. An exclusion system using cellulose diacetate or polyester covers provided comparable growing conditions for the plants, except for the presence or absence of ambient UV‐B radiation, respectively. The second experiment studied the effect of elevated levels of UV‐B on eight cultivars of two legume and two grass species in the greenhouse under simulated sward conditions. Natural lighting with sufficient supplemental light was used to provide ideal growing conditions for a 16‐h day length. Separate sets of UV lights were installed to provide UV‐B levels at approximately the same intensity as would be found in mid summer, and 33% and 66% more than this value. A fourth treatment consisted of removing UV‐B radiation by using a polyester filter. Plant production was measured in both experiments. In 1994, field herbage yields from all young grass and legume seedlings were not significantly affected by the exclusion of ambient UV‐B radiation, with the exception of alfalfa. Intra‐specific variations with alfalfa yields were found for reduced levels of UV‐B radiation. In general, these trends persisted as stands matured during two post seeding years. In the second experiment, no significant differences were observed for all tested species with increasing levels of UV‐B radiation, except with some alfalfa cultivars and one birdsfoot trefoil cultivar. Collectively, these results demonstrate that in the northern latitudes young and mature plants of the studied species are resistant to current and potentially higher levels of solar UV‐B radiation, with the exception of some alfalfa cultivars. The yield of these cultivars increased under enhanced levels of UV‐B radiation in the greenhouse and decreased when UV‐B was excluded in the field.

On the mechanism of action of thiamin enzymes, Crystal structure of 2-(α-hydroxyethyl)thiamin pyrophosphate (HETPP). Complexes of HETPP with zinc(II) and cadmium(II) - Gerasimos Malandrinos; Maria Louloudi; Cristiana A. Mitsopoulou; Ian S. Butler; Robert Bau; N. Hadjiliadis (JBIC Journal of Biological Inorganic Chemistry, 1998)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)